Latin America – 2015: the right wave (International relations and international law Journal, 2018)
The article is devoted to the analysis of elections past in key countries of the region in 2015 and their impact on international relations on regional and global scales. As a result of the presidential and parliamentary elections in Argentina and Venezuela the internal political configuration in these key for the continent countries has changed seriously transforming general development trend of Latin America: the rise to power of the conservative center-right parties reinforces tendency to minimize the «Bolivarian revolution,» declared by Hugo Chavez in the beginning of the XXI century. This trend has been strengthened by events in Brazil, where Dilma Rousseff has barely escaped impeachment procedure, and in Bolivia, where President Evo Morales has failed to achieve consent of the people to bring about changes in the constitution, allowing the current president to stand for a third term.Key words: Latin America, neo-populism, the «Bolivarian revolution», kirchnerism.